2014
DOI: 10.1074/jbc.m114.596221
|View full text |Cite
|
Sign up to set email alerts
|

A Sensory Complex Consisting of an ATP-binding Cassette Transporter and a Two-component Regulatory System Controls Bacitracin Resistance in Bacillus subtilis

Abstract: Background: BceS-like histidine kinases strictly require BceAB-like ABC transporters for sensing of peptide antibiotics. Results: BceAB of Bacillus subtilis interacted with BceS in vivo and in vitro and specifically bound the substrate peptide bacitracin. Conclusion: Complex formation with the ABC transporter affects the activity of the histidine kinase. Significance: Histidine kinase and ABC transporter form a sensory complex for the detection of peptide antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 46 publications
4
99
0
Order By: Relevance
“…We performed whole genome sequencing of the DAP‐R derivatives in both strain backgrounds in order to identify genetic changes associated with development of DAP‐R (Table ). Interestingly, both strains developed mutations in the sensing module of the two‐component regulatory system YxdJK, a BceAB‐like system previously linked to bacitracin (BAC) resistance in Bacillus subtilis and E. faecalis and chlorhexidine tolerance in E. faecium (Dintner et al , ; Gebhard et al , ; Prieto et al , ). The YxdJK system encodes a sensor histidine kinase ( yxdK ) and cognate response regulator ( yxdJ ), which positively regulates a putative ABC transporter (YvcRS, required for signal transduction along with YxdK) and a second transporter (YxdLM) responsible for the BAC resistance phenotype (Gebhard et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…We performed whole genome sequencing of the DAP‐R derivatives in both strain backgrounds in order to identify genetic changes associated with development of DAP‐R (Table ). Interestingly, both strains developed mutations in the sensing module of the two‐component regulatory system YxdJK, a BceAB‐like system previously linked to bacitracin (BAC) resistance in Bacillus subtilis and E. faecalis and chlorhexidine tolerance in E. faecium (Dintner et al , ; Gebhard et al , ; Prieto et al , ). The YxdJK system encodes a sensor histidine kinase ( yxdK ) and cognate response regulator ( yxdJ ), which positively regulates a putative ABC transporter (YvcRS, required for signal transduction along with YxdK) and a second transporter (YxdLM) responsible for the BAC resistance phenotype (Gebhard et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…High-level glutamate transporter operon expression may provide MT45 with more glutamate for the efficient synthesis of surfactin. More importantly, ABC transporters together with the neighbouring TCS have been recognized as detoxification systems for resistance against antimicrobial peptides in many Firmicutes bacteria3839. Surfactin works as an antibiotic by attacking the bacterial cell membrane9.…”
Section: Resultsmentioning
confidence: 99%
“…Initial evidence from cell wall-less L-forms of B. subtilis showed that the Bce system is triggered in the absence of cell wall biosynthesis (Wolf et al 2012), arguing for a 'drug-sensing' mechanism of stimulus perception. This view was supported by in vitro results indicating that BceB is able to bind bacitracin directly (Dintner et al 2014). In vivo results, on the other hand, argued for BceB binding UPP and even suggested that this transporter might play a role as a UPP flippase of the cycle (Kingston et al 2014).…”
Section: Drug Sensing Versus Target Sensingmentioning
confidence: 92%
“…Moreover, a single point mutation in the Walker B motif of the ATPase BceA (exhibiting a highly reduced rate of ATP hydrolysis) also abolished signaling via BceRS, showing that ATP hydrolysis, and thus active transport of bacitracin, is required for stimulus perception (Rietkötter et al 2008). Bacterial two-hybrid analyses together with in vitro pulldown assays further showed that the permease BceB forms a complex with the histidine kinase BceS (Dintner et al 2014) (Fig. 3a), and amino acid residues crucial for this contact have been identified in the permease BceB (Kallenberg et al 2013).…”
Section: The Bcers-bceab Complex Acts As An Antibiotic Flux Sensormentioning
confidence: 95%